Institutional Development of Irrigation Management Based on The Local Wisdom in Indonesia - Popi Rejekiningrum; Budi Kartiwa (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
During 1980-1997, the management of water resources was done with a supply-driven approach.  This approach results in the expensive maintenance of water resources and the disregarded resources utilization of environmental sustainability.  Since 1998, The Government of Indonesia began to reform institutional irrigation with the financing supported by the World Bank. However, the institutional reforms of the irrigation have not yet reflected the exact changes as expected. Therefore, it is necessary to study the process of strengthening the institutional management of irrigation based on the local wisdom through the inventory of history series of irrigation management policy and empowerment of capacity building and institutional program of irrigation management. This paper presents an effort to develop the institutional irrigation management by exploring the local wisdom in the community. It can be used as a guide for future sustainable management of irrigation. JEL Classification: B30, Q15, Q25